Dowry and Provision of Gift Money in Malay Community from the Perspective of Islamic Jurisprudence and Islamic Family Law in Malaysia: (Amalan Pemberian Mas Kahwin dan Wang Hantaran dalam Kalangan Masyarakat Melayu: Perspektif Fiqh dan Undang-Undang Keluarga Islam di Malaysia) (Kanun: Jurnal Undang-undang Malaysia, 2022)
This article explores the Malay community's marriage traditions, namely the distribution of dowry and provision of gift money by the husband to his wife. According to custom, during the marriage ceremony in most states, the dowry rate is mentioned in the ijab and kabul, but the amount of provision of gift money is not mentioned even though both are recorded in the marriage certificate. In addition to dowry, the provision of gift money is viewed as two similar elements, both of which are monetary in nature but have distinct individual names.Dowry is required to be given by the husband to his wife according to the Quran and Sunnah. However, the provision of gift money is a tradition and 'urf in marriage that is practiced by the Malay community. Their differential pronunciations pose concerns about the real status and function of provision of gift money as well as the legal implications for their right and ownership. Therefore, this article aims to pinpoint and discuss the law and the status of both dowry and provision of gift money in accordance with Islamic jurisprudence and Islamic family law. The article employed library research to expound on the writings of jurists of Islamic jurisprudence as well as textual studies on the provisions of law related to the issue concerned. The study found that a lack of understanding of the law governing dowry and provision of gift money, as well as incoherence in the marriage certificate's record of marriage details, have resulted in misunderstandings within the community while also affecting the right and ownership of both gifts.Keywords: Dowry, provision of gift money, tradition, Islamic jurisprudence, Islamic Family Law, ownershipFull text: PDF